Interview Questions for Lupe Anguiano - Doyle, Alicia; Ventura County Star (Ventura County Star)
Alicia Doyle, writer of Ventura County Star, e-mails Lupe Anguiano upon knowing that she is receiving the first annual RA RA Awards and would like to write a story to get in the newspaper. A response e-mail from Lupe Anguiano is followed.